Do investors learn from the past? Evidence from follow-on equity issues - Duca, Eric (Journal of Corporate Finance, 2016)
Equity offerings are usually characterized by large information asymmetries between issuers and investors. Using a sample of repeat equity issues, I examine whether investors form beliefs of corporate intentions based on the outcomes of past offerings by the same firm. I document a robust negative relationship between post-issue returns and underpricing in a follow-on offering. The evidence is most consistent with the idea that market feedback influences investor beliefs of a firm's investment opportunities in a subsequent offering. Feedback is particularly important when it contains information about investment opportunities that managers do not possess. The results also provide insights into the impact of market feedback on the cost of issuing further equity.